Evaluación de la Educación Superior en Brasil: políticas y prácticas - Dias Sobrinho, José (Revista Complutense de Educación, 2007)
This paper presents a few aspects of the implementation of Brazilian higher education evaluation policies and practices in the last few years. Emphasis is put on the close relationship between the transformation projects in higher education and their corresponding evaluation programs. A few contextual characteristics and some distinctions between the main evaluative models and their links to the public policies that seek to transform higher education are presented. Despite the difficulties, some important advances are also found, especially at the present moment.